Education, occupation and income inequalities in obesity among Portuguese women and men : Evidence from national health surveys (1998-2019) - Valente, Berta; Severo, Milton; Gerdtham, Ulf-Göran ; 0000-0002-0647-7817; Fraga, Sílvia; Araújo, Joana (Social Science and Medicine, 2025)
INTRODUCTION: This study examined trends in socioeconomic inequalities in obesity among Portuguese women and men using data from National Health Surveys (NHSs). METHODS: We analysed weighted data from adults aged 20-64 years from the 1998/1999 (n = 20,581), 2005/2006 (n = 13,088), 2014 (n = 7284), and 2019 (n = 5959) NHSs. Obesity was defined as body mass index (BMI) ≥30 kg/m 2, based on self-reported height and weight. Socioeconomic position (SEP) was assessed by education, occupation, and income. Absolute and relative inequalities were measured using the slope index of inequality (SII) and relative index of inequality (RII), derived from log-binomial regression models. SEP indicators were ranked using RIDIT scores. Models included interactions between RIDIT, sex, and survey year, and were adjusted for age and region. RESULTS: Absolute educational inequalities [SII(95%CI)] widened slightly for both women [1998:-0.182(-0.206; -0.158); 2019:-0.206(-0.281; -0.131)] and men [1998:-0.074(-0.0.98; -0.050); 2019:-0.121 (-0.193; -0.050)]. Among women, occupation-SII increased until 2005/2006 and then stabilised. Among men, occupation-SII increased steadily, particularly between 2014 and 2019. Income-SII were smaller but evident among women, peaking in 2014 and declining in 2019. Among men, SII-income were less consistent and generally smaller. RII trends mirrored those of SII, with relative inequalities decreasing slightly among women and increasing among men, especially for education and occupation. The gender gap in both absolute and relative inequalities narrowed over time, particularly for occupation. CONCLUSION: Socioeconomic inequalities in obesity persist, with obesity being disproportionally concentrated among individuals with lower education, income and less differentiated occupations. Overall, women consistently faced greater inequalities than men.
Copyright © 2025 The Author(s). Published by Elsevier Ltd.. All rights reserved.